Molecular epidemiology of Bordetella pertussis and analysis of vaccine antigen genes from clinical isolates from Shenzhen, China - Shuang Wu; Qinghua Hu; Chao Yang; Haijian Zhou; Hongyu Chen; Yanwei Zhang; Min Jiang; Yuxiang He; Xiaolu Shi (BMC, 2021)
Abstract Background Although pertussis cases globally have been controlled through the Expanded Programme on Immunization (EPI), the incidence of pertussis has increased significantly in recent years, with a "resurgence" of pertussis occurring in developed countries with high immunization coverage. Attracted by its fast-developing economy, the population of Shenzhen has reached 14 million and has become one of the top five largest cities by population size in China. The incidence of pertussis here was about 2.02/100,000, far exceeding that of the whole province and the whole country (both < 1/100,000). There are increasing numbers of reports demonstrating variation in Bordetella pertussis antigens and genes, which may be associated with the increased incidence. Fifty strains of Bordetella pertussis isolated from 387 suspected cases were collected in Shenzhen in 2018 for genotypic and molecular epidemiological analysis. Methods There were 387 suspected cases of pertussis enrolled at surveillance sites in Shenzhen from June to August 2018. Nasopharyngeal swabs from suspected pertussis cases were collected for bacterial culture and the identity of putative Bordetella pertussis isolates was confirmed by real-time PCR. The immunization history of each patient was taken. The acellular pertussis vaccine (APV) antigen genes for pertussis toxin (ptxA, ptxC), pertactin (prn) and fimbriae (fim2 and fim3) together with the pertussis toxin promoter region (ptxP) were analyzed by second-generation sequencing. Genetic and phylogenetic analysis was performed using sequences publicly available from GenBank, National Institutes of Health, Bethesda, MD, USA ( https://www.ncbi.nlm.nih.gov/genbank/ ). The antimicrobial susceptibility was test by Kirby-Bauer disk diffusion. Results Fifty strains of Bordetella pertussis were successfully isolated from nasopharyngeal swabs of 387 suspected cases, with a positivity rate of 16.79%, including 28 males and 22 females, accounting for 56.0% and 44.0% respectively. Thirty-eight of the 50 (76%) patients were found to be positive for B. pertussis by culture. Among the positive cases with a history of vaccination, 30 of 42 (71.4%) cases had an incomplete pertussis vaccination history according to the national recommendation. Three phylogenetic groups (PG1-PG3) were identified each containing a predominant genotype. The two vaccines strains, CS and Tohama I, were distantly related to these three groups. Thirty-one out of fifty (62%) isolates belonged to genotype PG1, with the allelic profile prn2/ptxC2/ptxP3/ptxA1/fim3-1/fim2-1. Eighteen out of fifty (36%) isolates contained the A2047G mutation and were highly resistant to erythromycin, and all belonged to genotype PG3 (prn1/ptxA1/ptxP1/ptxC1/fim3-1/fim2-1), which is closely related to the recent epidemic strains found in northern China. Conclusions The positive rate of cases under one-year-old was significantly higher than that of other age groups and should be monitored. The dominant antigen genotypes of 50 Shenzhen isolates are closely related to the epidemic strains in the United States, Australia and many countries in Europe. Despite high rates of immunization with APV, epidemics of pertussis have recently occurred in these countries. Therefore, genomic analysis of circulating isolates of B. pertussis should be continued, for it will benefit the control of whooping cough and development of improved vaccines and therapeutic strategies.